The Relationship Between Self-efficacy and Intention to Engage in Premarital Sex Among Adolescent Students in Public Secondary Schools in Tanzania (Tanzania Journal for Population studies and Development, 2023)
The study examined the relationship between self-efficacy and intention to engage in pre-marital sex among adolescent students in public secondary schools in Tanzania. It employed a quantitative approach guided by correlation design, using structured questionnaires. Three hundred and fifty-seven (357) participants were involved: 172 males and 185 females. The results showed that 61.6% of the respondents had a reasonably high level of self-efficacy, while 70.1% had a lower level of intention to engage in premarital sex. It was also found that there was no statistical relationship between self-efficacy and intention to engage in premarital sex among adolescent students in public secondary schools (p=0.78>0.05). Therefore, the government—through the Ministry of Education, Science and Technology—should introduce self-efficacy programmes in the secondary school curriculum, which will help improve moral, social, cognitive and emotional qualities in adolescent students, so that they abstain from any risky sexual behaviours.